ANALISIS PENGALAMAN PENGGUNA DALAM MENGGUNAKAN LEARNING MANAGEMENT SYSTEM (LMS) AFRESTO DI SMP NEGERI 2 KUTA - Ni Nyoman Ayu Puspitawati (Pusat Penelitian dan Pengabdian Kepada Masyarakat, 2026)
This study aims to analyze the user experience (UX) of the Afresto Learning Management System (LMS) at SMP Negeri 2 Kuta using the User Experience Questionnaire (UEQ) method and in-depth interviews. As a digital learning support system, Afresto's effectiveness depends on the quality of experience perceived by its users. This research employs a mixed-method approach with a sample of 269 students and 16 teachers determined through stratified random sampling. The results reveal a significant User Experience Gap (UX Gap) between the two user groups. Teachers rated the system positively across all dimensions (Good to Above Average), finding it helpful for administrative tasks. Conversely, students rated the system negatively (Bad to Below Average), particularly in the Dependability (0.72) and Attractiveness (0.65) dimensions. These findings indicate that while the system is functional for teachers, it suffers from performance issues (errors during peak loads) and an unappealing interface for students. Recommendations include server optimization (load balancing), UI modernization, navigation redesign (task-centric dashboard), and the implementation of gamification to enhance student motivation.